Analisis Media Sosial Tiktok Terhadap Perubahan Tingkah Laku Siswa di SMPN 11 Maros Baru - Wahyuni Ramadani; Gilang Septiansyah; Rezkia Djohar; Muhammad Syukur; Ibrahim Arifin (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The current globalization period is experiencing very rapid progress, it is undeniable that the presence of the internet continues to be a necessity in everyday life, both in socialization activities, learning, business, and so on. It is inevitable that social media has a huge influence in a person's life. For people, especially teenagers, social media has become something addictive and it's hard not to open it every day. At the same time, while still in development, adolescents find their identity by socializing with peers at school. This study aims to study the influence of Tiktok social media on adolescents during the growth period, as well as to find out how Tiktok affects their behavior change. This study uses qualitative research methods to explore phenomena that occur in the field and understand the influence of Tiktok social media on changes in adolescent behavior in the natural adolescent environment, including the time and place of these changes. Researchers want to get deep and complex research results about these phenomena that are difficult to reveal by quantitative methods and do not require processing numbers and statistics. The object of this research is adolescents who are experiencing a period of growth, especially at SMPN 11 Maros Baru.